Technical elements for a necessary debate on income concentration measurements in Colombia (2020)
The objective of this work is to contribute elements about a “taboo” debate, a few years ago, since to speak of inequality was to promote the “class struggle”. The source of information is the Encuesta nacional de presupuestos de hogares and income tax returns. The combination of these two sources of information is necessary to make an approximation to the distribution of income in Colombia, considered the third most unequal country in the world. Similarly, high levels of income concentration are observed, as well as a middle class with a high probability of falling into poverty given the confinement, since 42% of it has an average income between 2 and 3 current legal minimum wages.